STUDENT INDIVIDUAL MANAGEMENT TECHNIQUES IN THE LEARNING PROCESS - Nur 'Adillah; Alfianti, Alfianti; Iswandi, Iswandi (Amanah Publishing, 2025)
Individual student management techniques are crucial in the classroom learning process. Each student has different characteristics, needs, and potentials, requiring teachers to manage each individual individually to ensure effective learning and optimal development. These management techniques aim to create a comfortable learning environment and support the development of each student's abilities. This study aims to examine student management techniques in the learning process. This research method utilizes literature review, combining expert opinions to draw conclusions. This study is a qualitative study, examining opinions from existing references. This research was developed through studies and analysis of individual student management techniques. Data analysis in qualitative research is conducted during data collection and after data collection has been completed within a specific period. In this case, the researcher took data related to the research title, namely individual student management techniques. After data reduction, the next step is to display the data. Data presentation is carried out in the form of brief descriptions, sections, relationships between categories, and the like. The results of this study indicate that individual student management techniques are an important approach in education that emphasizes understanding and paying special attention to the unique characteristics and needs of each student. With this technique, teachers can create a more personalized and effective learning environment, thus optimally encouraging student motivation, emotional development, and academic achievement. Furthermore, individual student management also strengthens teacher-student relationships through warm and open communication, which is crucial for creating a conducive and inclusive learning environment. However, implementing this technique is not without its challenges, one of which is the limited time and resources teachers have, which require systemic support for optimal implementation. The author also emphasizes the importance of balancing technology utilization with a humanistic approach to maintain personal interactions. With commitment and creativity from all parties, individual student management techniques are believed to be the foundation for a more humane, effective, and sustainable education in addressing the dynamic needs of students.